Klasifikasi Minat Jamaah terhadap Kajian Islami - Roro Fatikhin; Nuari Anisa Sivi; Wafiq Abdulloh (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
This study aims to analyze congregants’ interest in Islamic study sessions at Al-Ikhlas Mosque using a descriptive qualitative approach. Islamic study sessions play an essential role in enhancing religious understanding, character development, and social cohesion within the Muslim community. However, attendance levels tend to fluctuate due to various influencing factors. Data were collected through observations, interviews, and documentation to explore the perceptions, motivations, and experiences of the congregants. The findings reveal that congregants’ interest is shaped by several key factors, including the study theme, the lecturer’s delivery method, the timing of the sessions, mosque facilities, spiritual needs, and social encouragement from the surrounding community. Based on field data, congregants’ interest can be categorized into three levels: high, moderate, and low. This research is expected to assist mosque administrators in optimizing the implementation of Islamic study sessions by adjusting themes, selecting appropriate lecturers, and improving facility convenience.